2017
DOI: 10.1007/s40094-017-0240-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different alcohols, gelatinizing times, calcination and microwave on characteristics of TiO2 nanoparticles synthesized by sol–gel method

Abstract: In this work, nanoparticles of titanium dioxide (TiO 2 ) were synthesized by means of TiCl 4 as precursor. Effects of alcohol type, calcination, gelatinizing time and microwave exposure on the particle size, morphology, crystallinity and particle phase are studied using XRD patterns and SEM images. Results showed that alcohols such as ethanol increased the particle size; calcination increased the particle size and improved the crystallinity of particles. Microwave exposure of particles resulted in smaller part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The use of ethanol slowed down the chemical reaction, and hence the particles acquired a spherical shape with no agglomeration. Ethanol was used in other studies [38,39] and showed similar results with the current study. This phenomenon is probably due to the presence of smaller and more active -OH and -C 2 H 5 groups in ethanol, which is reported to be effective in eliminating water molecules [40] that cause more agglomeration to form larger molecules [39].…”
Section: Fesem/edx and Bet Analyses Of Caco 3 Particles Using Differe...supporting
confidence: 84%
See 1 more Smart Citation
“…The use of ethanol slowed down the chemical reaction, and hence the particles acquired a spherical shape with no agglomeration. Ethanol was used in other studies [38,39] and showed similar results with the current study. This phenomenon is probably due to the presence of smaller and more active -OH and -C 2 H 5 groups in ethanol, which is reported to be effective in eliminating water molecules [40] that cause more agglomeration to form larger molecules [39].…”
Section: Fesem/edx and Bet Analyses Of Caco 3 Particles Using Differe...supporting
confidence: 84%
“…Ethanol was used in other studies [38,39] and showed similar results with the current study. This phenomenon is probably due to the presence of smaller and more active -OH and -C 2 H 5 groups in ethanol, which is reported to be effective in eliminating water molecules [40] that cause more agglomeration to form larger molecules [39]. The enhancement of the particle size upon the addition of ethanol was reported to be due to the reduction of the energy of atomization as a consequence of the decrease in the vapour pressure of the solution, owing to their slow evaporation [41,42].…”
Section: Fesem/edx and Bet Analyses Of Caco 3 Particles Using Differe...supporting
confidence: 84%
“…Further treatment of the wet gel could also convert the gel into dense glass or ceramic, which offers high purity, uniform nanoparticles at low-temperature processing, molecular homogeneity, and fine particle size. However, parameters such as the addition of reactants, temperature or calcination, pH, and solubility of chemicals in the solvents affect the molecular homogeneity of the gel (Bahar et al 2017).…”
Section: Solgel Methodsmentioning
confidence: 99%
“…TiO 2 colloidal solution was prepared by hydrolysis of titanium tetraisopropoxide (TTIP) by Kavitha et al (2014) who reacted 1 cm 3 of titanium tetraisopropoxide with 4 cm 3 of acetic acid. The resultant mixture was hydrolyzed with 10 cm 3 of distilled water and vigorously stirred for 1 h. This was kept in an oven at 100 °C and then annealed at 300 and 600 °C for 1 h. Bahar et al (2017) synthesized TiO 2 nanoparticles using TiCl 4 as the precursor. TiCl 4 was added to ethanol, isopropanol, and butanol at a molar ratio of TiCl 4 /alcohol of 1:10.…”
Section: Synthesis and Mechanism Of Tiomentioning
confidence: 99%
“…Indeed, the morphology of the TiO 2 NPs was found to be influenced by the volume ratio between alcohol and TiO 2 precursor, as well as by the nature of alcohol selected as a solvent for the specific synthetic route. As an example, Bahar et al reported that syntheses performed in ethanol lead to larger NPs (33 nm) than those obtained in butanol (26 nm) and isopropanol (30 nm) [22]. Duymaz et al investigated the effect of the solvent composition, testing two different solvents (ethyl alcohol or water) to dissolve the TiO 2 precursor.…”
Section: Sol-gel Methodsmentioning
confidence: 99%